2014
DOI: 10.1039/c4ay01655f
|View full text |Cite
|
Sign up to set email alerts
|

Fast screening of polycyclic aromatic hydrocarbons using trapped ion mobility spectrometry – mass spectrometry

Abstract: In the present paper, we showed the advantages of trapped ion mobility spectrometry coupled too mass spectrometry (TIMS-MS) combined with theoretical calculations for fast identification (millisecond timescale) of polycyclic aromatic hydrocarbons (PAH) compounds from complex mixtures. Accurate PAH collision cross sections (CCS, in nitrogen as a bath gas) are reported for the most commonly encountered PAH compounds and the ability to separate PAH geometric isomers is shown for three isobaric pairs with mobility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 27 publications
3
63
0
Order By: Relevance
“…[118121] In addition, changes in the conformational space can be observed as a function of the desolvation process and upon activation prior to the IMS-MS measurements. Previous work using TIMS-MS has shown the possibility to trap a wide mobility range from small molecules to small proteins[122, 123]; however, it was also demonstrated that the trapping efficiency is a function of the electrode geometry, bath gas profile and electrical confining parameters (e.g., radiofrequency value and amplitude).…”
Section: Resultsmentioning
confidence: 99%
“…[118121] In addition, changes in the conformational space can be observed as a function of the desolvation process and upon activation prior to the IMS-MS measurements. Previous work using TIMS-MS has shown the possibility to trap a wide mobility range from small molecules to small proteins[122, 123]; however, it was also demonstrated that the trapping efficiency is a function of the electrode geometry, bath gas profile and electrical confining parameters (e.g., radiofrequency value and amplitude).…”
Section: Resultsmentioning
confidence: 99%
“…A significant number of the small molecules CCS values consists of aromatic hydrocarbons. 98,119,139,162164 Starting in the 1990s, interest in inorganic compounds (metal salts, atomic and molecular clusters) began to emerge. Very few inorganic compound CCS values were reported between 2000 and 2010, with a resurgence of interest starting in 2013 which were primarily focused on gaining fundamental insights into the structures of inorganic salt and metal clusters.…”
Section: Ccs Coverage Over Timementioning
confidence: 99%
“…9 Photoionization has been used for the analysis of chemical warfare agents with standalone ion mobility spectrometers, mainly as a non-harmful and "soft" replacement for the radioactive 63 Ni source. 23 18,27 Yet to date no studies are published that take advantage of an APPI/APLI-IMS-FTMS setup.…”
Section: Introductionmentioning
confidence: 95%